A systematised literature review: Can low-dose whole-body computed tomography replace a radiographic skeletal survey when investigating paediatric non-accidental injury?. (December 2021) - Doyle, Edel; Dimmock, Matthew; Lee, Kam; Ng, Jessica; Bassed, Richard
Highlights: A radiographic skeletal survey is the current 'gold standard' for the radiological investigation of suspected non-accidental injury. No articles discussing the use of whole-body CT skeletal surveys in living children were found. This empty literature review has identified a gap in knowledge. Further ethical research should be undertaken to provide the evidence based to support a change in clinical practice.